Quality of life and its associated factors among knee osteoarthritis patients - Arif, Mohd Faizal Mohd (2017)
Introduction: Osteoarthritis is the most common form of arthritis around the globe. The aim of knee osteoarthritis treatment is to alleviate pain, delay progression of osteoarthritis, improvement in mobility, walking as well as improvement in the quality of life. Despite the clear goal of treatment mentioned, quality of life is the least considered or often neglected aspect in the overall management of patients with knee osteoarthritis. Objectives: To determine the quality of life and its associated factors among knee osteoarthritis patients. Methodology: A cross-sectional study was conducted from 1st June 2014 until 30th October 2014 at the orthopaedic clinic in Universiti Sains Malaysia Hospital (HUSM). Systematic random sampling was applied based on attendance list in orthopaedic clinic, HUSM. A set of questionnaires which includes case report form and the Malay version of Osteoarthritis Knee and Hip Quality of Life (OAKHQOL) questionnaire was given to patients before determining their body mass index (BMI) and reviewing their latest knee radiograph. Data analysis was done using SPSS Version 22. The overall quality of life among knee osteoarthritis were expressed by using mean OAKHQOL score for each domain while the associated factors that affecting the quality of life were analysed by using general linear regression analysis. Result: The mean quality of life among patient with knee osteoarthritis were average. The worse domain was a social functioning domain with a mean scoreof 59.1 (SD 26.31) and the least affected domain was mental health domain with the mean score of 35.7 (SD 22.42). Increasing BMI was consistently associated with worsening of almost all domains of OAKHQOL which include physical activity (CI 0.50, 1.68), mental health (CI 0.17, 1.49), pain (CI 0.24, 1.58) and professional activity (CI 0.34, 1.94) except for social support which showed an improvement with increasing BMI (CI -2.39, -0.63). Social functioning was not associated with any studied variables. An ever-used glucosamine associated with worsening score on physical activity (CI 1.51, 14.99), mental health (CI 1.79, 17.17) and pain (CI 2.98, 18.68) domains. Longer duration of knee osteoarthritis and bilateral involvement of knee were both associated with worse sexual activity (CI 0.42, 2.59); (CI 3.68, 20.37) and relationship item score (CI 0.28, 2.48); (CI 2.83, 19.79). Higher education status appears to have a better score in mental health (CI -33.24, -7.42) and pain (CI -32.11, -5.75). domain. An ever used NSAIDs was associated with poorer score in sexual activity item (CI 0.20, 17.11). Higher grade of knee osteoarthritis by Kellgren Lawrence grading of knee osteoarthritis have worse professional activity item score (CI 0.03, 24.49). Conclusion: The quality of life among patients with knee osteoarthritis in this study was average. Increasing BMI was consistently associated with worsening of almost all domains of OAKHQOL, except for social functioning. Social functioning was not associated with any studied variables. Variables that had an association with at least one domain of OAKHQOL were education status, grade of knee osteoarthritis, medication usage (glucosamine or NSAIDs), duration of knee pain and knee involvement (unilateral or bilateral).